The Synergy of Hydrogen Bond and Entanglement of Elastomer Captures Unprecedented Flaw Insensitivity Rate. Issue 16 (22nd January 2023) - Zeng, Xiangliang; Xu, Lu; Xia, Xinnian; Bai, Xue; Zhong, Cheng; Fan, Jianfeng; Ren, Linlin; Sun, Rong; Zeng, Xiaoliang
Abstract: Elastomers are regarded as one of the best candidates for the matrix material of soft electronics, yet they are susceptible to fracture due to the inevitable flaws generated during applications. Introducing microstructures, sacrificial bonds, and sliding cross‐linking has been recognized as an effective way to improve the flaw insensitivity rate ( R insen ). However, these elastomers still prone to failure under tensile loads with the presence of even small flaws. Here, this work reports a polybutadiene elastomer with unprecedented R insen via the synergy of hydrogen bond and entanglement. The resulting polybutadiene elastomer exhibits a R insen  ≈1.075, which is much higher than those of reported elastomers. By molecular chain interaction and molecular chain conformation analysis, this work demonstrates that the synergistic effect of hydrogen bond dissociation and entanglement slip in the polybutadiene elastomers during stretching leads to the high R insen . Using polybutadiene elastomer as matrix of thermal interface materials, this work demonstrates effective heat transfer for strain sensor and electronic devices. In addition, cytocompatibility of the elastomers is verified by cell proliferation and live/dead viability assays. The combination of outstanding biocompatible and excellent mechanical properties of the elastomers creates new opportunities for their applications in electronic skin. Abstract : A polybutadiene elastomer with unprecedented Rinsen via the synergy of hydrogen bond and entanglement is fabricated. The resulting polybutadiene elastomer exhibits an unprecedented Rinsen ≈1.075, which is much higher than those of reported elastomers. The combination of outstanding biocompatible and extraordinary mechanical properties of the elastomers creates new opportunities for their applications in electronic skin.